THE EMERGING TECHNOLOGIES OF DIGITAL PAYMENTS AND ASSOCIATED SERVICES - W, Angelin; S, Sangeetha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The interaction between finance and technology, facilitated by the internet, has sparked the rise of digital payment technologies. These technological advancements in the payment industry serve as the basis for achieving financial inclusion. However, despite the continuous progress and potential of transitioning towards digital payments and connecting the population to the pervasive digital landscape, there are critical issues that must be addressed in order to establish a more harmonious, inclusive, and sustainable cashless society. This study aims to provide a comprehensive literature review on the emerging digital payment technologies and the challenges they entail. Through a systematic review of existing empirical studies, this research proposes a state-of-the-art classification of digital payment technologies, encompassing four categories: card payment, e-payment, mobile payment, and cryptocurrencies. Furthermore, the paper identifies key challenges in digital payment technologies, which can be broadly categorized into social, economic, technical, awareness, and legal themes. The classification and categorization of payment technologies, along with the associated challenges, can serve as a valuable resource for both researchers and practitioners in understanding, clarifying, and developing a cohesive digital payment strategy.